Serving the needy from the greedy: Reviewing Diakonia in African neo-Pentecostalism - Tagwirei, Kimion (In die Skriflig/In Luce Verbi, 2023)
When the economy turned downwards across most African nations over the past two decades hitherto today, multifarious neo-Pentecostal churches correspondingly multiplied in and beyond the Global South. While it ordinarily appeared to be a revolutionary Africanisation of Christian revival through massive indigenous evangelisation and establishment of new denominations, countless leading prophetic apostles were selfishly enriching themselves paradoxically in the world’s headquarters of poverty, where the needy are multiplying and dying. Most diaconal publications engage with classical and mainline ecclesiology. Notably, minimum scholarly attention has been given to diakonia in African neo-Pentecostalism. Applying grounded theory, researching through the available literature, observation and the media, this article sought answers to issues that problematise diakonia in African neo-Pentecostalism. It unfolded and concluded that, instead of being other-centred, the generality of neo-Pentecostal leaders are self-centred, greedy opportunists exploiting the needy. Consequently, it recommended theological education, ecumenical engagement, and the establishment of an inclusive and independent regulatory body to enlighten and empower gospel ministers to revise their hermeneutics, theologies, ecclesiologies, governance and administration for the accomplishment of diakonia , as well as other dimensions of missio ecclesiae . Contribution: This article contributes to the transformational development of African Spiritualities and Leadership in Ecclesiology and Missiology by reviewing diakonia in African neo-Pentecostalism.
free